PRINCIPLES OF DIAGNOSIS AND TREATMENT OF ACUTE PURULENT-DESTRUCTIVE LUNG DISEASES (Intent Research Scientific Journal, 2023)
The article presents basic information reflecting current issues of pathogenesis and modern methods of treatment of purulent-destructive lung diseases. The article is a review of literature data on this issue we have collected over the past 20 years. Nowadays, it became known that a pathogenetic point of view, in all cases of acute purulent lung destruction is determined by the combination and interaction of three main factors: 1) acute infectious inflammatory process in the pulmonary parenchyma; 2) violation of bronchial 36 patency; 3) a violation of the blood flow leading to necrosis of the lung tissue. Unfortunately, the existing classification, valuation trends, proposed methods of treatment of acute suppurative destructive processes in the lung is practically not taken into account the state of non-respiratory activity of the lungs. In general, the presented information on modern achievements in the study of pathogenesis, the development of new methods of surgical treatment of patients with acute purulent-destructive lung diseases with the use of "small surgery" techniques showed that many issues related to improving the final results remain unresolved. Keywords: acute lung abscess, gangrene of lung, etiopathogenesis, prevalence, diagnostic and treatment method.